Students perspectives on switching from online to face-to-face learning environments after the COVID-19 pandemic - Masyitha Wahid; Firdaus Firdaus; Nur Amaliah; Ariandi Ariandi; Firman Firman; M. Irfan; Arlinda Puspita Sari; Muhammad Rizaldi Trias Jaya Putra Nurdin‬ (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
After around two years of having online learning, students in the universities have to come back to face-to-face learning mode as it was before the pandemic. This setting also applied to the biology education study program of Universitas Sulawesi Barat. The current study investigated the students’ perspective on changing online to face-to-face learning after COVID-19. It is a qualitative descriptive study with nine students as respondents from the classes of 2019, 2020, and 2021. The instrument used was an interview guide consisting of indicators regarding online teaching and learning features, assessment, and interactions that students needed to experience in face-to-face settings but would like to. In addition, students' perceptions of the advantages and disadvantages of the shift from online to offline learning were also assessed. The data analysis was performed in three stages: data reduction, data display, and drawing a conclusion or data verification. The result showed that several things they would like to have as it was during online learning were (1) have electronic materials, online-games-based learning, and more time to complete the assignments, (2) get various types of assessments including via online platforms (3) to have online applications or media to discuss learning materials and submit assignments. (4) In addition, for the advantages, the practicums could be conducted in laboratories, they felt more concentrated during offline classes, and became more confident to apply IT skills during offline settings, while the disadvantages were feeling anxious and fear to interacting during offline class and trouble to listen to lecturers’ class while having masks. Overall, students feel face-to-face learning is way more effective and efficient but suggested blended learning as an interesting mode in the learning and teaching implementation.